NILAI-NILAI PENDIDIKAN MODERASI BERAGAMA HABIB HUSEIN JA’FAR AL-HADAR: ANALISIS MAKNA DAN MEDIA KONTEN INSTAGRAM @HUSEIN_HADAR - Abu Aman; Subaidi (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Instagram has become a platform where information flows rapidly and widely, ranging from entertainment and educational content to religious discourse. In the context of education, narratives about religious moderation in Indonesia vary—some are persuasive, while others are provocative. Ideally, provocative content on social media should be countered with persuasive content. This paper highlights a figure of religious moderation who advocates for Islam as a mazhab cinta (school of love), namely Husein Ja'far Al-Hadar (@husein_hadar). Specifically, it focuses on one of his posts dated August 16, 2023, with the caption: “Anyone who is not your brother in religion, ethnicity, or other identities is your brother in Indonesia.” This writing explores how Husein Ja'far Al-Hadar's Islam mazhab cinta is reflected through the lens of meaning and media in that particular post. Additionally, it investigates the extent to which the values of religious moderation are embodied in his message, using semiotic and structuralist analysis. It also examines the denotative and connotative meanings of the image showing a habib and a bante standing together in traditional religious attire. Based on relevant theories and conceptual frameworks, the post can be analyzed as a representation of religious moderation values consistent with the social routines and everyday activities Husein Ja'far Al-Hadar regularly advocates. Ultimately, the core of Husein Ja'far Al-Hadar’s approach to religious moderation lies in the application of religious values related to faith and worship through his concept of Islam as a mazhab cinta